Transformation of sedimentary and colloidal phosphorus across the land‒sea margin received effluents from agricultural and municipal activities. (15th December 2022) - Hsu, Liang-Ching; Tzou, Yu-Min; Liao, Wen-Han; Teah, Heng Yi; Liu, Yu-Ting
Abstract: The transformation, transport, and release of phosphorus (P) are highly subject to anthropogenic activities and complex biochemical interactions. Its bioavailability and recalcitrance are generally regulated by P forms, arousing imposition for the accurate identification of chemical speciation. Here, P K -edge X-ray absorption near edge structure spectroscopy was exploited to determine the molecular P species on colloids, canal sludge, and coastal sediments collected in the area receiving mixed effluents from agricultural and municipal activities. Although Fe(III)-bonded P [Fe(III)–P] dominated the P inventory for colloids and sludge collected near the agricultural area, its proportion on colloids was approximately half of that on the sludge, suggesting the emerging contribution of other P species such as Al–P, Fe(II)–P, and organic-P (org-P) to carry colloidal P. Proportions of Fe(III)–P on colloids and sludge both declined seaward, yet the maximum P loss from colloids was derived from the org-P. The organic matter degradation plausibly drove the reduction of SO4 and Fe(III), leading to the prominent increase in FeS and the conversion of org-P to authigenic P. While Al–P accounted for a comparable proportion of colloidal P inventory to that of Fe(III)–P in adjacent coastal wetlands, the proportion of Fe(II)–P showed the greatest increase on colloids in the transition from fresh-to saltwater. Collective results attest to the significance of Fe(II) and Al in partitioning colloidal and sedimentary P, which should be taken into account to improve the assessment of the P dynamics and eutrophication risk. Graphical abstract: Image 1 Highlights: P retention is controlled by adsorption/coprecipitation with Fe(III) hydroxides. The Fe(III) had a reduced role on colloidal and sedimentary P retention seaward. Organic P contributed the greatest colloidal P loss in the seaward transition zone. The Fe(II)- and Al–P became more significant in the seaward transition zone. Fe(II) and Al are considered while assessing the P dynamics and eutrophication risk.